How Shore Orientation and Substrate Type Structure Lichen Communities in the Boundary Waters Canoe Area Wilderness. - Naus, Christopher J.; Wiley, Jasmine R.; Sisco, Matthew J.; Dins, Jamie K. (My University, 2009)
Rock inhabiting lichens are important pioneer species in the aquatic-terrestial transition zone of lakeshore habitats. To investigate how substrate type, slope and aspect influenced lichen communities, we surveyed the rocky shores of glacial lakes within the Boundary Waters Canoe Area Wilderness (BWCAW)of northern Minnesota.
Color poster with text, images, and diagrams.
Keywords: Lichens--Environmental aspects; Lichens--Minnesota--Boundary Waters Canoe Area; Lichen communities--Environmental aspects; Lichen communities--Minnesota--Boundary Waters Canoe Area; Posters